Factors Affecting forest Volume and Biomass at Watershed Level: a Study in Annapurna Conservation Area, Nepal - Gurung, Naba Raj; Sankhayan, Prem Lall; Hofstad, Ole; Sitaula, Bishal K. (Indian Forester, 2002)
A study was carried out in Mardi watershed in Nepal to estimate the stem volume and biomass and analyze the factors responsible for their variations in different forest types.Tree height and diameter at breast height were measured in nine sample quadrants each in Mixed Hardwood Forest (MHF) and Oak Forest (OF) and 13 sample quadrants in High Mountain Mixed Forest (HMMF) for 56 tree species.The per hectare stem volume and biomass of trees in HMMF and OF was 2 to 3.5 times higher than that in MHF.The mean volume per hectare was 2.3 and 2.7 times higher and the stem density 2.5 and 2.7 times higher in the conservation area as compared to regional and national averages. Mean volume and biomass in the forests with high accessibility and low altitude differed significantly from those with medium and low accessibility and medium and high altitude.Mean volume and biomass did not vary significantly by s]ope classes and aspects.Distance, altitud.e and slope explained up to 93 percent of the total variation in OF biomass. The usefulness of the study lies in providing baseline data for analyzing the changes in forest health, measured in terms of biomass and volume.